SELEKTIVITAS HIDROKARBON PADA SINTESIS FISCHER–TROPSCH BERBASIS SYNGAS KULIT KOPI MENGGUNAKAN SOFTWARE ASPEN PLUS - Benazir Zulfana Anwar; Arif Rahman Saleh; Rany Puspita Dewi; Tri Retno Setiyawati (ELEMEN : JURNAL TEKNIK MESIN, 2026)
Indonesia’s continued dependence on non-renewable fossil energy sources contrasts with the underutilization of New and Renewable Energy (NRE), despite its abundant resource availability. One promising yet underexploited NRE source is coffee husk biomass, which is generated in large quantities as a by-product of plantation activities. This study aims to analyze hydrocarbon selectivity in the Fischer–Tropsch (FT) synthesis process using syngas derived from coffee husk gasification through thermochemical modeling in ASPEN Plus. Simulations were conducted at an operating temperature of 240ºC and a pressure of 25 bar using various thermodynamic methods. The results indicate that the product distribution is dominated by heavy hydrocarbons (C₅⁺), with selectivity values of 9.881% for the Grayson model, 5.341% for BK10, and the highest value of 1.333×10¹% obtained using the Peng–Robinson equation of state, while light hydrocarbons exhibit selectivity in the order of 10⁻⁶–10⁻³. The Peng–Robinson model demonstrates the most representative performance for predicting liquid heavy hydrocarbons from biomass-based Fischer–Tropsch synthesis.